Ultrasensitive Detection of Antiseptic Antibiotics in Aqueous Media and Human Urine Using Deep UV Resonance Raman Spectroscopy - Domes, Christian; Domes, Robert; Popp, Juergen; Pletz, Mathias W.; Frosch, Torsten (Analytical Chemistry, 2017)
Deep UV resonance Raman spectroscopy is introduced as an analytical tool for ultrasensitive analysis of antibiotics used for empirical treatment of patients with sepsis and septic shock, that is, moxifloxacin, meropenem, and piperacillin in aqueous solution and human urine. By employing the resonant excitation wavelengths λexc = 244 nm and λexc = 257 nm, only a small sample volume and short acquisition times are needed. For a better characterization of the matrix urine, the main ingredients were investigated. The capability of detecting the antibiotics in clinically relevant concentrations in aqueous media (LODs: 13.0 ± 1.4 μM for moxifloxacin, 43.6 ± 10.7 μM for meropenem, and 7.1 ± 0.6 μM for piperacillin) and in urine (LODs: 36.6 ± 11.0 μM for moxifloxacin, and 114.8 ± 3.1 μM for piperacillin) points toward the potential of UV Raman spectroscopy as point-of-care method for therapeutic drug monitoring (TDM). This procedure enables physicians to achieve fast adequate dosing of antibiotics to improve the outcome of patients with sepsis.
CRIS-Team Scopus Importer:2023-04-20